The use of mobile-aided learning in education of local anesthesia for the inferior alveolar nerve block - Mladenović, Raša; Pereira, Leonardo; Djordjević, Filip; Vlahović, Zoran; Mladenović, Kristina; Cvetković, Andrijana; Martinović, Brankica; Mladenović, Jovan; Popovski, Julie (Vojnosanitetski pregled, 2021)
Background/Aim. Dental education has developed over the years, and various technologies have been included. Considering the fact that mobile devices are an imperative of modern time, the aim of our research was to evaluate effectiveness of Mobile-Aided Learning on practical administering the inferior alveolar nerve block (IANB). Methods. This prospective study involved 34 students who were randomly divided into two groups: G1 (control) group with 16 students and G2 (study) group with 18 students. Students of both groups previously successfully completed theoretical and practical training provided by the curriculum. For the purpose of additional education, students of the G2 group used a mobile application for 3D simulation of local anesthesia (Mobile-Aided Learning) outside the dental office for a period of one semester. After that, all students completed a post-clinical questionnaire. Results. The average time for performing anesthesia by participants in the G1 group was 70.54 ± 20.16 seconds, while in the G2 group it was 57.13 ± 17.45 seconds, which was significantly shorter (p ˂ 0.05). A successful anesthesia application was higher in the G2 group (83.3%) compared to the G1 group (75%). The results of the post-clinical test questionnaire also indicated difference in the mean values of the responses to all questions, which was in favor of the G2 group participants. Conclusion. Application of Mobile-Aided Learning showed a significantly higher efficiency in student education for practical implementation of the IANB.
Keywords: anesthesia, dental; mandible; nerve block; students; cell phone; learning; computer simulation